A Comparison of Short- and Long-Term Therapeutic Outcomes of Infliximab- versus Tacrolimus-Based Strategies for Steroid-Refractory Ulcerative Colitis - Katsuya Endo; Motoyuki Onodera; Hisashi Shiga; Masatake Kuroha; Tomoya Kimura; Keiichiro Hiramoto; Yoichi Kakuta; Yoshitaka Kinouchi; Tooru Shimosegawa (Gastroenterology Research and Practice)
Background/Aims. Antitumor necrosis factor antibodies and calcineurin inhibitors have shown good therapeutic efficacy for steroid-refractory ulcerative colitis (UC). Although some studies have compared the efficacy of infliximab (IFX) and cyclosporin A, there are no published studies comparing IFX and tacrolimus (Tac). This study aimed to compare therapeutic efficacies between IFX- and Tac-based strategies for steroid-refractory UC. Methods. Between July 2009 and August 2013, 95 patients with steroid-refractory UC received either IFX (n=48) or Tac (n=47) in our hospital. In the IFX group, the patients continued to receive maintenance treatment with IFX. In the Tac group, patients discontinued Tac treatment up to 3 months and subsequently received thiopurine. We retrospectively compared the therapeutic outcomes between the groups. Results. There was no significant difference in the colectomy-free rate, clinical remission rate, and clinical response rate at 2 months between the groups. However, relapse-free survival was significantly higher in the IFX group than in the Tac group (p<0.001; log-rank test). The proportions of serious adverse events did not differ between the groups. Conclusion. The findings of our study showed that IFX and Tac have similar short-term therapeutic efficacy for steroid-refractory UC. Maintenance treatment with IFX, however, yields better long-term outcomes than Tac-thiopurine bridging treatment.